Spectrophotometric Determination of Methyl Paraben in Pharmaceutical Formulations by Oxidative Coupling Reaction - Abdul Majeed Khorsheed Ahmed; Abdulla Salim Khazaal; Alyea Hussain Ahmed (Tikrit Journal of Pure Science)
A simple and sensitive spectrophotometric method was developed for the determination of  Methyl Paraben via oxidative coupling with the 2,4-Dinitrophynel hydrazine in the presence of N-bromosuccinimid in a basic medium, Absorbance of the obtained coloured products was measured at the corresponding optimum wavelengths (600 nm), Beer’s law is obeyed over the concentration of 2.0-20 μg.ml-1, and The molar absorptivity of  (6253 L.mole-1.cm-1), Sandell,s sensitity index of (0.02433 µg.cm-2). The detection limits were (0.34 μg.ml-1), with a linear regression correlation coefficient of  (0.9947)  and  recovery range from (98.96–103%). The proposed method has been applied successfully to determine Methyl Paraben in pharmaceutical preparations and cosmetic formulations.